Pharmacokinetics and Clinical Outcomes of Generic Tacrolimus (Hexal) Versus Branded Tacrolimus in De Novo Kidney Transplant Patients: A Multicenter, Randomized Trial. Issue 11 (November 2017) - Arns, Wolfgang; Huppertz, Andrea; Rath, Thomas; Ziefle, Stephan; Rump, Lars C.; Hansen, Anita; Budde, Klemens; Lehner, Lukas J.; Shipkova, Maria; Baeumer, Daniel; Kroeger, Irena; Sieder, Christian; et al.
Abstract : Background: Scrupulous comparison of the pharmacokinetic and clinical characteristics of generic tacrolimus formulations versus the reference drug (Prograf) is essential. The pharmacokinetics of the Tacrolimus Hexal (TacHexal) formulation is similar to Prograf in stable renal transplant patients, but data in de novo patients are lacking. Methods: De novo kidney transplant patients were randomized to generic tacrolimus (TacHexal) or Prograf in a 6-month open-label study. Results: The primary end point, the dose-normalized area under the curve0-12h at month 1 posttransplant, was similar with TacHexal or Prograf; back-transformed geometric means of adjusted log-transformed values (analysis of variance) were 18.99 ng·h·L −1 (TacHexal) and 20.48 ng·h·L −1 (Prograf) (ratio, 1.08; 90% confidence interval, 0.84-1.38; P = 0.605). The dose-normalized peak concentration geometric means at month 1 was also comparable between treatments (ratio, 1.16; 90% confidence interval, 0.88-1.54; P = 0.377). There were no relevant differences in other pharmacokinetic parameters at month 1 or in area under the curve0-4h and trough concentration when measured at months 3 and 6. The adjusted change in mean estimated glomerular filtration rate from baseline to month 6 (Nankivell) was noninferior for TacHexal versus Prograf using observed values (47.7 vs 38.6 mL/min per 1.73 m 2, P < 0.001) and was superior based on observed values ( P = 0.044) but not using last observation-carried forward method. Rates of biopsy-proven acute rejection (5.7% vs 7.9%), adverse events, and serious adverse events were similar with TacHexal or Prograf. Conclusion: Tacrolimus pharmacokinetics is similar with TacHexal and Prograf early after kidney transplantation. Efficacy and safety in this limited data set were comparable, with at least equivalent graft function under TacHexal. Abstract : In a population of 73 kidney transplant recipients randomized to receive de novo either generic tacrolimus (Hexal) or branded tacrolimus (Prograf), the authors report on similar tacrolimus pharmacokinetics as well as similar efficacy and safety during the first 6 months of follow-up. Supplemental digital content is available in the text.